Self-Similarity, Leaf Litter Traits, and Neighborhood Predicting Fine Root Dynamics in a Common-Garden Forest - Fischer, Dylan G.; Dickson, Brett G.; Whitham, Thomas G.; Hart, Stephen C. (Frontiers in Environmental Science, 2019)
While individual tree genotypes are known to differ in their impacts on local soil development, the spatial genetic influence of surrounding neighboring trees is largely unknown. We examine the hypothesis that fine root dynamics of a focal tree is based on the genetics of the focal tree as well as the genetics of neighbor trees that together define litter inputs to soils of the focal tree. We used a common garden environment with clonal replicates of individual tree genotypes to analyze fine root production, turnover and allocation with respect to modeled neighborhood: 1) foliar mass, 2) foliar condensed tannins (CT), 3) genetic identity of trees, and 4) genetic dissimilarity of neighbors. In support of our central hypothesis, we found that the presence of genetically dissimilar trees and high leaf CT contributions to the soil predicted increased fine root production. In fact, the modeled effects of neighbors accounted for ~90% of the explanatory weight of all models predicting root production. Nevertheless, the ultimate fate of those roots in soil (turnover) and the balance of fine roots relative to aboveground tree mass were still more predictable based on the genetics of the individual focal trees (explaining 99% of the variation accounted for by models). Our data provide support for a method allowing a comparison of the relative effects of individuals versus spatial neighborhood effects on soils in a genetic context. Such comparisons are important for placing plant-soil feedbacks in a genetic and evolutionary framework since neighbors can decouple feedbacks between an individual and the surrounding environment.